Deep-sea terrigenous organic carbon transfer and accumulation: Impact of sea-level variations and sedimentation processes off the Ogooue River (Gabon). (August 2017) - Mignard, Salomé Lou-Andréa; Mulder, Thierry; Martinez, Philippe; Charlier, Karine; Rossignol, Linda; Garlan, Thierry
Abstract: Sedimentary, isotopic and bulk geochemical proxies measured in sediment samples of five gravity cores collected in the distal part of the Ogooue turbidite system (around 4000 m-depth) were used to develop a conceptual model to describe the accumulation of terrigenous organic matter (OM) during the last 200, 000 yrs BP in the eastern part of the Gulf of Guinea. This model takes into account the influence of the different depositional processes (turbiditic vs hemipelagic sedimentation), geomorphological features and sea-level variations. Total organic carbon (TOC) and the stable organic carbon isotopes of the OM (δ 13 C) variability follow the highstand/lowstand (interglacial/glacial) cyclicity with a very low accumulation rate of terrigenous OM during periods of high sea-level and higher accumulation rate during period of low sea-level. A sea-level of 80–120 m below present day seems to favor the transfer of terrigenous sediments to the deep offshore environment through the turbidite system and thanks to the connection of the canyons heads with the river system presently located at the shelf edge at −120 m water depth. In this system, terrigenous OM matter delivered by the river accumulate in the sediments via two main processes. Indeed, a part of the terrigenous OM settles in combination with the finest particles forming hemipelagites, while another part, formed of very well preserved land plant debris, is transported and deposited far offshore with turbidity currents. The proportion of terrigenous OM accumulated due to turbidity currents is important as it can represent more than 70% of the carbon accumulated during sea-level lowstand. Moreover, terrigenous OM seems to preferentially accumulate in the levees and the lobes of the system notably due to the higher frequency of organic-rich turbidites. This study demonstrates that gravity flows, influenced by the sea-level variations, can significantly affect the terrigenous OM budget of the deep offshore Atlantic margins and that channel-levee complexes as well as turbidite lobes can be regarded as good sink for terrestrial organic carbon. These processes should be taken into consideration in the context of source rocks exploration but also for the estimation of the general carbon accumulation in ocean sediment. Highlights: High terrigenous organic carbon content in deep offshore sediments. Turbidite currents are efficient to transport and bury high amounts of terrigenous organic particles. Channel-levee complexes and lobes accumulate preferentially particulate organic carbon. Low-sea levels enhance the accumulation of terrigenous organic carbon. Geomorphology impact the organic matter accumulation in the distal part of the turbidite system.